Influence of Species, Growing Site, and Postharvest Leaf Handling on the Yield and Chemical Composition of Cajuput Oil (Melaleuca spp.) from Seram Island, Indonesia - Imanuel Berly Delvis Kapelle; Fensia Analda Souhoka; Nini Munirah Renur (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Cajuput (Melaleuca spp.) is a high-value non-timber forest product in Seram Island, Maluku. The quality of cajuput oil is primarily determined by its 1,8-cineole (eucalyptol) content, which is influenced by genetic, environmental, and raw material factors. This study analyzed the effects of species, growing location, and raw material condition on the yield and chemical composition of oil derived from Melaleuca leucadendra and Melaleuca cajuputi collected from Hatusua and Eti villages, using distillation and GC-MS analysis. The results showed that fresh leaves yielded higher amounts than dried leaves. The highest yield was obtained from M. leucadendra from Eti (1.022%), while the lowest yield was recorded from dried leaves (0.008%). M. leucadendra oil was dominated by eucalyptol (56.62–58.50%), whereas M. cajuputi was dominated by methyleugenol (81.61%) with a lower yield (0.1213%), reflecting differences in genetically controlled metabolic pathways. Environmental factors influenced yield and minor compounds without altering the dominant constituents. Overall, the quality and quantity of cajuput oil are determined by the interactions among genetic, environmental, and post-harvest factors. The use of fresh raw materials, appropriate species or chemotypes, and optimal growing locations is key to improving oil quality and ensuring consistent production.